Diagnosis dan penatalaksanaan nodul tiroid tunggal: Sebuah laporan kasus - Nyoman Pramudita; Anak Agung Gede Budhi Kusuma (Intisari Sains Medis, 2021)
Background: Thyroid nodules are abnormal lesions in the form of masses or nodules found in thyroid tissue. Thyroid nodules have a prevalence of about 8% in the adult population. A single thyroid nodule is asymptomatic and is generally discovered incidentally on physical examination or imaging. Diagnosis is made by physical examination, imaging examination and cytopathological examination. The management of a single thyroid nodule can be done by providing interventional therapy and surgery. The purpose of this case report is to describe the diagnosis and management of a single thyroid nodule case in Wangaya General Hospital.Case description: A 52-year-old male patient came to the Surgical Clinic at Wangaya General Hospital with complaints of a lump on the left neck in the past eight months. The lump is felt to be enlarged and painless. The patient's diagnosis was confirmed by cytologic examination, which revealed a follicular nodule with a benign tendency. The patient was given surgical therapy in the form of left thyroidectomy.Conclusion: Single thyroid nodule is quite rare. Treatment of a single thyroid nodule was adjusted according to the results of the cytologic examination. The prognosis for a single thyroid nodule with benign cytology results is generally reasonable. However, it is necessary to follow-up the patient considering the false negative value of the cytological examination. Latar belakang: Nodul tiroid adalah lesi abnormal berupa massa atau nodul yang terdapat dalam jaringan tiroid. Nodul tiroid memiliki prevalensi sekitar 8% pada populasi dewasa. Nodul tiroid tunggal bersifat asimtomatik dan umumnya ditemukan secara tidak sengaja saat pasien melakukan pemeriksaan fisik atau pencitraan. Penegakan diagnosis dilakukan dengan pemeriksaan fisik, pemeriksaan pencitraan dan pemeriksaan sitopatologi. Penatalaksanaan nodul tiroid tunggal dapat dilakukan dengan pemberian terapi intervensi dan pembedahan. Tujuan pelaporan kasus ini adalah untuk menjabarkan diagnosis dan penatalaksanaan pada salah satu kasus nodul tiroid tunggal di RSUD Wangaya.Deskripsi kasus: Seorang pasien laki-laki berusia 52 tahun datang ke Poli Bedah RSUD Wangaya dengan keluhan benjolan pada leher kiri sejak 8 bulan yang lalu. Benjolan dirasakan membesar dan tidak nyeri. Diagnosis pasien ini dikonfirmasi melalui pemeriksaan sitologi yang menunjukkan suatu nodul folikular dengan kecenderungan ke arah jinak. Pasien diberikan terapi pembedahan berupa tiroidektomi sinistra.Simpulan: Nodul tiroid tunggal cukup jarang terjadi. Terapi nodul tiroid tunggal disesuaikan dengan hasil pemeriksaan sitologi. Prognosis nodul tiroid tunggal dengan hasil sitologi jinak umumnya baik, namun perlu dilakukan follow-up terhadap pasien menimbang nilai negatif palsu dari pemeriksaan sitologi.